Production of cytokine and chemokines by human mononuclear cells and whole blood cells after infection with Trypanosoma cruzi - Karine Rezende-Oliveira; Ronaldo Rodrigues Sarmento; Virmondes Rodrigues Junior (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: The innate immune response is the first mechanism of protection against Trypanosoma cruzi, and the interaction of inflammatory cells with parasite molecules may activate this response and modulate the adaptive immune system. This study aimed to analyze the levels of cytokines and chemokines synthesized by the whole blood cells (WBC) and peripheral blood mononuclear cells (PBMC) of individuals seronegative for Chagas disease after interaction with live T. cruzi trypomastigotes. METHODS: IL-12, IL-10, TNF-α, TGF-β, CCL-5, CCL-2, CCL-3, and CXCL-9 were measured by ELISA. Nitrite was determined by the Griess method. RESULTS: IL-10 was produced at high levels by WBC compared with PBMC, even after incubation with live trypomastigotes. Production of TNF-α by both PBMC and WBC was significantly higher after stimulation with trypomastigotes. Only PBMC produced significantly higher levels of IL-12 after parasite stimulation. Stimulation of cultures with trypomastigotes induced an increase of CXCL-9 levels produced by WBC. Nitrite levels produced by PBMC increased after the addition of parasites to the culture. CONCLUSIONS: Surface molecules of T. cruzi may induce the production of cytokines and chemokines by cells of the innate immune system through the activation of specific receptors not evaluated in this experiment. The ability to induce IL-12 and TNF-α contributes to shift the adaptive response towards a Th1 profile.